Local Wisdom for Ecotourism Development In Bogor - Dyah Prabandari; Ricky Avenzora; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
The development that occurred in the Bogor city is currently feared will have an impact on shifting authenticity of existing regional identity. Regional identity that still exists is one manifestation of local wisdom carried out by the community. This research was conducted to identify the type of local wisdom that is still done by the community to be assessed and analyzed by One Score One Criteria Scoring System method to be proposed as the regional identity of Bogor City. Languang Badong, Lodong Bogoran, Wayang Hihit, Rengkong Hatong and Tauge Goreng are local wisdom of art and culinary aspect in Bogor City. The ecotourism concept put forward to maintain the local wisdom in Bogor City. Keywords: ecotourism, lLocal wisdom, regional identity